Medium: Wizualizacja pierwszej warstwy narracyjnej: Odkrywanie - Koprowicz, Jacek (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
A director’s analysis of the narrative layers in the film Medium allows one see, among other things, the construction of individual elements of the film. Through an analysis of the construction of particular scenes and the relations between them within the story, the text describes the visual narrative structure of the first layer, i.e. “discovery” (the next layers are: confirmation, confrontation and fulfillment). Within the horror genre, this layer is an essential element in building a dramaturgical structure and in influencing the viewers’ reactions (including the visual pleasure of “discovering”).

Reżyserska analiza warstw narracyjnych w filmie Medium pozwala zobaczyć, między innymi, budowę poszczególnych elementów filmu. Dzięki analizie budowy poszczególnych scen i relacji między nimi w obrębie fabuły, tekst opisuje wizualną strukturę narracyjną pierwszej warstwy, tj. ”odkrycie" (kolejne warstwy to: potwierdzenie, konfrontacja i spełnienie). W horrorach warstwa ta jest istotnym elementem w budowaniu struktury dramaturgicznej i wpływaniu reakcjach widzów (łącznie z wizualną przyjemnością "odkrycia").
The Film Medium. Visualization of the First Layer of the Narrative Level: Discovery
Jacek Koprowicz, PWSFTviT w Łodzi, Medium: Wizualizacja pierwszej warstwy narracyjnej: Odkrywanie, The Film Medium. Visualization of the First Layer of the Narrative Level: Discovery, „Images” 2012, vol. XI: (Re)imagining the Past, red. A. Mrozewicz i J. Czaja, nr 20, s. 101-132., ISSN 1731-450x, język: polski
Keywords: horror; analysis; narrative layers; visual narrative; dramaturgical structure; analiza; warstwa narracyjna; narracja wizualna; struktura dramaturgiczna